BALANCING IP RIGHTS AND COMPETITION LAW THROUGH PATENT POOLS IN INDONESIA: A COMPARATIVE ANALYSIS - Sugarda, Paripurna; Wicaksono, Muhammad Rifky (Journal of Central Banking Law and Institutions, 2022)
In 1998, Heller and Eisenberg, discovered the ‘tragedy of the anticommons’ which occurs when there are numerous patent holders who must give their consent before a technology can be used. Consequently, where excessive property rights are claimed, some technology is underused, and innovation is stunted. To solve this issue, the patent owners can aggregate their patents into a single ‘patent pool.’ However, there are significant anticompetitive harms which may arise from such a practice. Hence, this paper aims to answer the question of whether the creation of patent pools as an antidote to the ‘tragedy of anticommons’ would be at the cost of competition law. This research found that it is possible to use patent pools as a solution to the tragedy of the anticommons, while preventing harm to competition. The Indonesian Competition Authority can take inspiration from EU regulations to create a ‘safe harbor’ for companies who engage in technology transfer agreements if they meet the market share thresholds. They can also improve the framework for analyzing patent pools by laying out the different categories of patents to ascertain the different levels of harm they bring to competition.